3 - L’éclatement de la Haute-Volta et de la Côte d’Ivoire de 1932 à 1947 - Joseph Abo Kobi, (Afrika Zamani, 2022)
Erected as a French colony in 1919, the territory of Upper Volta will undergo a dismemberment in 1932 because of the lack of economic interest it represents for the colonial administration. Given its economic potential, Côte d’Ivoire thus becomes the main beneficiary of this administrative act. This attachment of a large part of Upper Volta, zone to Côte d’Ivoire a frontier, seems to be useful for its exploitation. But this dismemberment is disputed by the Voltaics, headed by the Mossi. The various actions of Moro Naba’s protest and the demands of the population, combined with the will of the administration and the support of the Catholic clergy, led to the revival of Upper Volta in 1947.